ChCDC25 Regulates Infection-Related Morphogenesis and Pathogenicity of the Crucifer Anthracnose Fungus Colletotrichum higginsianum - Yan, Yaqin; Tang, Jintian; Yuan, Qinfeng; Gu, Qiongnan; Liu, Hao; Huang, Junbin; Hsiang, Tom; Zheng, Lu (Frontiers in Microbiology, 2020)
The fungal pathogen, Colletotrichum higginsianum, causes a disease called anthracnose on various cruciferous plants. Here, we characterized a Saccharomyces cerevisiae CDC25 ortholog in C. higginsianum, named ChCDC25 (CH063_04363). The ChCDC25 deletion mutants were defective in mycelial growth, conidiation, conidial germination, appressorial formation, and invasive hyphal growth on Arabidopsis leaves, resulting in loss of virulence. Furthermore, deletion of ChCDC25 led to increased sensitivity to cell wall stress, and resulted in resistance to osmotic stress. Exogenous cAMP and IBMX treatments were able to induce appressorial formation in the ChCDC25 mutants, but abnormal germ tubes were still formed. The results implied that ChCDC25 is involved in pathogenicity by regulation of cAMP signaling pathways in C. higginsianum. More importantly, we found that ChCDC25 may interact with Ras2 and affects Ras2 protein abundance in C. higginsianum. Taken together, ChCDC25 regulates infection-related morphogenesis and pathogenicity of C. higginsianum. This is the first report to reveal functions of a CDC25 ortholog in a hemibiotrophic phytopathogen.